Comparison of Pulse Rate Variability and Heart Rate Variability for Hypoglycemia Syndrome - Okkesim, Şükrü; Çelik, Gamze; Yıldırım, Mustafa S.; Ilhan, Mahmut M.; Karaman, Özcan; Taşan, Ertuğrul; Kara, Sadık (Methods of Information in Medicine, 2016)
Background: Heart rate variability (HRV) is a signal obtained from RR intervals of electro -cardiography (ECG) signals to evaluate the balance between the sympathetic nervous system and the parasympathetic nervous system; not only HRV but also pulse rate va -riability (PRV) extracted from finger pulse plethysmography (PPG) can reflect irregularities that may occur in heart rate and control procedures.Objectives: The purpose of this study is to compare the HRV and PRV during hypogly -cemia in order to evaluate the features that computed from PRV that can be used in detection of hypoglycemia.Methods: To this end, PRV and HRV of 10 patients who required testing with insulininduced hypoglycemia (IIHT) in Clinics of Endocrinology and Metabolism Diseases of Bezm-i Alem University (Istanbul, Turkey), were obtained. The recordings were done at three stages: prior to IIHT, during the IIHT, and after the IIHT. We used Bland-Altman analysis for comparing the parameters and to evaluate the correlation between HRV and PRV if exists.Results: Significant correlation (r > 0.90, p < 0.05) and close agreement were found between HRV and PRV for mean intervals, the root-mean square of the difference of successive intervals, standard deviation of successive intervals and the ratio of the low-to-high frequency power.Conclusions: In conclusion, all the features computed from PRV and HRV have close agreement and correlation according to Bland-Altman analyses’ results and features computed from PRV can be used in detection of hypoglycemia.
Keywords: Insulin-induced hypoglycemia; finger pulse plethysmography; electrocardiography